HUBUNGAN LAYANAN BIMBINGAN INFORMASI KARIR DENGAN KEMATANGAN PERENCANAAN KARIR SANTRI KELAS XII - Ayu Auliya (Realita : Jurnal Bimbingan dan Konseling, 2022)
Adolescents of SMA/Aliyah class XII are individuals who are considered adults and can be better prepared to face the world of work or career. However, some of these teenagers have not received counseling services optimally, especially career guidance, this is because many schools still ignore the function of counseling services which result in unpreparedness in understanding careers optimally. The purpose of this study was to determine the effect of career information guidance services on career planning maturity of class XII students at MA Darunna’im Lebak-Banten. This research method uses the Quantitative Corelational method. And is population study, with a total of 92 students from class XII Madrasah Aliyah Darunna’im Kalanganyar, Lebak, Banten.